2015
DOI: 10.1088/0268-1242/30/8/085020
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing radiation effect on metal–ferroelectric–insulator–semiconductor memory capacitors

Abstract: A theoretical model was developed to investigate the ionizing radiation effect on the electrical characteristics of metal-ferroelectric-insulator-semiconductor (MFIS) structure capacitors under exposure to radiation and under post-irradiation conditions. In this model, the radiation-induced degradation in the ferroelectric layer, oxide layer and silicon dioxide interface were considered, and the radiation effect of the silicon substrate was also taken into account to accommodate the dose rate effect. The model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The simulation result exhibited a PCE of 9.88% for the device employing NiO x and further verified by the experimental consequence with a 500 nm thick perovskite active layer . The devices integrated with Cu 2 O and 500‐nm‐thick perovskite active layer were simulated to achieve an efficiency over 13% due to the high mobility of Cu 2 O and optimized perovskite thickness …”
Section: Inorganic Hole Transporting Materials In Pscssupporting
confidence: 61%
“…The simulation result exhibited a PCE of 9.88% for the device employing NiO x and further verified by the experimental consequence with a 500 nm thick perovskite active layer . The devices integrated with Cu 2 O and 500‐nm‐thick perovskite active layer were simulated to achieve an efficiency over 13% due to the high mobility of Cu 2 O and optimized perovskite thickness …”
Section: Inorganic Hole Transporting Materials In Pscssupporting
confidence: 61%
“…These phenomena are the consequence of several physical mechanisms including: ionizing particle-material interaction inducing ionizing energy loss, electron-hole pair generation and separation, transport of carriers along the electric field lines in dielectrics, charge trapping in preexisting defects and/or reaction with dangling bonds to generate interface traps at silicon/dielectric interfaces [40,41]. Such effects can be induced in a wide range of electronic devices [37,38,42,43] irradiated with a variety of ionizing particles like energetic photons, protons, heavy ions or electrons. In most cases, radiation-induced positive charge trapping in dielectrics and interface traps creation can thus modify the electrical characteristics of MOSFETs depending on the transistor geometry, the type of dielectrics, the doping levels used in the active silicon region.…”
Section: Basics Of Tid Effects In Mos Devicesmentioning
confidence: 99%
“…The two lateral gates efficiently screen electrostatic potential modifications that could occur at the fin/BOX interface making narrow SOI multiple-gate FETs naturally tolerant to TID. Figure 8 synthetizes TID results presented in [41][42][43]68] showing the W FIN dependence of various SOI multiple-gate architectures. Except data presented by Colinge et al [64] which are obtained using γ-rays irradiations, all other results presented in figure 8 are obtained using 10 keV-x-rays irradiations [69].…”
Section: Soi Multiple-gate Fetsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, ferroelectric memory technologies have attracted great interest due to the reported radiation tolerance of ferroelectric materials. Due to the aforementioned challenges in FeFETs integrated with traditional ferroelectric materials, previous research mainly focused on the radiation effects on ferroelectric thin films. Only a few works have been devoted to studying the impact of radiation on FeFET device characteristics. Yan et al investigated the TID effects in FeFETs integrated with SrBi 2 Ta 2 O 9 thin films and found that the TID radiation would cause severe threshold voltage ( V TH ) shift and memory window (MW) degradation. , In 2019, Chen et al first reported the TID effect on memory characteristics of Hf 0.5 Zr 0.5 O 2 (HZO)-based FeFETs . They found that the MW of HZO-based FeFETs did not degrade for the dose to 1 Mrad­(Si), but the program/erase (P/E) cycling properties (i.e., endurance properties) showed non-negligible degradation owing to the radiation.…”
Section: Introductionmentioning
confidence: 99%